2010
DOI: 10.1159/000313642
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Amniotic Fluid Index after Maternal Oral Hydration in Pregnancies with Fetal Gastroschisis: Initial Observations

Abstract: Objective: To evaluate the effect of maternal oral hydration on amniotic fluid index (AFI) in pregnancies with fetal gastroschisis. Methods: AFI was evaluated at 24-hour intervals, during 4 consecutive days, under a continuous maternal oral water hydration regimen, in singleton pregnancies with isolated fetal gastroschisis. Results: Nine pregnancies were examined at a mean gestational age of 31.6 weeks (±1.4) and mean maternal daily oral water intake was 3,437 (±810) ml. Mean AFI on days 0–3 were 13.2 (±2.9), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…A simple and innocuous method to correct the tendency to oligohydramnios seems to be the maternal oral hydration. 43 It has been suggested, indeed, that a glass of water per hour while awake would significantly increase the amount of amniotic fluid.…”
Section: Prenatal Diagnosis and Management Of Pregnancymentioning
confidence: 99%
“…A simple and innocuous method to correct the tendency to oligohydramnios seems to be the maternal oral hydration. 43 It has been suggested, indeed, that a glass of water per hour while awake would significantly increase the amount of amniotic fluid.…”
Section: Prenatal Diagnosis and Management Of Pregnancymentioning
confidence: 99%
“…Conflict between a study conducted by Yan‐Rosenberg et al 15 and previous studies led us to design this study. Previous studies showed the beneficial effect of maternal hydration in pregnancies with normal and decreased amniotic fluid volumes 6 – 12 , 19 24 . Yan‐Rosenberg et al 15 found that hydration increased the amniotic fluid index, as did the authors of the other studies.…”
Section: Discussionmentioning
confidence: 80%
“…Several studies have been conducted to support the use of oral or intravenous maternal hydration to increase the amount of amniotic fluid, with the research being performed under a variety of clinical scenarios, including normal pregnant volunteers, maternal hypovolemia, third‐trimester oligohydramnios, preterm rupture of membranes, and pregnancies complicated by anomalies such as gastroschisis 6 – 12 . The authors of those studies found an increased amniotic fluid index after hydration treatment.…”
mentioning
confidence: 99%
“…Detailed fetal anomaly and echocardiography scans were performed to confirm the abnormality and investigate associated malformations. Follow-up scans were scheduled to reevaluate the abdominal wall defect, bowel aspect, fetal growth, amniotic fluid volume and fetal well-being [3,10]. At each visit, fetal biparietal diameter, occipitofrontal diameter, head circumference (HC) and AC as well as femur length (FL) measurements were obtained according to standard techniques [11] and recorded in a computer database.…”
Section: Methodsmentioning
confidence: 99%